Wastewater Treatment of the Cracker Industry Using the Phytoremediation Method with Water Lettuce (Pistia stratiotes) Plants - Basransyah; Iitra Achbar Sahdian; Norita Ariyanti (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Cracker-industry wastewater contains substantial organic matter and suspended solids that may pollute the environment when discharged without adequate treatment. This study aimed to characterize cracker-industry wastewater, evaluate the phytoremediation effectiveness of water lettuce (Pistia stratiotes), and determine the effects of plant mass and contact time on total suspended solids (TSS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), dissolved oxygen (DO), and pH. A batch-system experiment was conducted using plant masses of 400 and 600 g, alongside a control, with contact times of 0, 3, 6, and 9 days. The initial wastewater characteristics were 168 mg/L TSS, 492.8 mg/L COD, 8.02 mg/L DO, and a pH of 6.5. The findings demonstrate that phytoremediation using P. stratiotes effectively reduced TSS, COD, and BOD concentrations and improved wastewater quality. After nine days, the highest TSS removal efficiency was 84% with 600 g of plant biomass, resulting in a final concentration of 27.5 mg/L. The highest COD removal efficiency was 63% with 600 g of plant biomass, producing a final concentration of 182.05 mg/L, whereas the highest BOD removal efficiency was 75% with 400 g of plant biomass, resulting in a final concentration of 21.30 mg/L. Contact time significantly affected COD and BOD reductions and changes in pH, while plant mass had no significant effect. The study concludes that P. stratiotes has considerable potential as a simple, economical, and environmentally sustainable phytoremediation agent for cracker-industry wastewater. These findings provide practical evidence for developing low-cost biological wastewater-treatment strategies for small-scale food-processing industries.